MuleSoft for Salesforce developers a practical guide to deploying MuleSoft APIs and integrations for Salesforce enterprise solutions - Sawant, Akshata; Alphonse, Arul Christhuraj (Packt Publishing Ltd., 2025)
Salesforce developers often need help with complex integrations to manage multi-cloud environments, data mapping, data security, API scalability, and real-time integration issues. Written by industry veterans with 20+ years of experience, this revised edition will help you overcome these challenges and unlock data with MuleSoft. In this second edition, you'll learn about MuleSoft's newest IDE (aka Anypoint Code Builder) and its tools and capabilities. The chapters will show you how to use AI-enabled APIs to maximize productivity, integration of Data Cloud with MuleSoft, Mule APIs with AI agents, and Mule AI Chain connectors. You'll grasp the fundamentals of APIs and integration and confidently design your APIs, while also utilizing a no-code visual editor for API design to build your Mule applications using MuleSoft's Anypoint Code Builder. The chapters will teach you about data transformation, API management, deployment models, and MuleSoft's security features. Progressively, you'll leverage MuleSoft connectors to integrate with Salesforce, Data Cloud, and other systems. You'll explore AI-driven integrations and automation, and get practical tips to ace MuleSoft interviews and achieve MCD Level 1 certification. By the end of this book, you'll be able to implement the entire API lifecycle and manage complex integrations with MuleSoft like a pro.
Includes bibliographical references and index
Keywords: Application program interfaces (Computer software); Computer software -- Development; Interfaces de programmation d'applications; APIs (interfaces)